(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: This study is based on the results of the initial observation that the performance of employees government environments Eastern District of Siau indicated relatively low. This condition is presumably related to the implementation of policies not optimal development of human resources quality civil servants in the region. Thus, this study aims to: (1) Examine the impact of the quality of human resource development policy environment of government civil servants Eastern District of Siau Island District Sitaro. (2) to analyze differences in the performance of employees government environments Eastern District of Siau Island District Sitaro between before and after participating in education and training (Training). This research applies descriptive and quantitative approach combined with a qualitative approach, the sample of respondents purposively set as many as 44 employees. After analyzing the data collected by applying the product moment correlation technique and simple linear resgresi. The results of data analysis showed that (1). The average implementation of the development policy of human resource quality of civil servants and the gains of government employees districts Siau Timur, both are in the category of "medium" or not achieve optimal results. (2) Policy development of quality human resources dilingkingan government civil servants Eastern District of Siau positive and significant impact on employee performance improvement. The conclusions that can be drawn from this research is that an employee who has been following the development program through education and training (training) showed a much higher performance than before following the employee development program. Advice can be given is conveyed to the government of Regency Sitaro for more intensive follow-include civil servants, either at the district or sub-district / village in educational activities and training, and much needed concrete efforts of the local government district Sitaro in the form of rotation, transfer, training in the workplace and others. Keywords: Policy penghembangan HR, employee performance